Early‐stage diffuse panbronchiolitis in a young patient confirmed by video‐assisted lung biopsy: A case report. (8th May 2017) - Watanabe, Yasutaka; Kawabata, Yoshinori; Iwai, Yuki; Kudo, Fumiaki; Kawamura, Rumi; Miwa, Chihiro; Nagai, Yoshiaki; Koyama, Shinichiro
Abstract: A 29‐year‐old man presented with sputum and cough, which were pointed out by his neighbors. A high‐resolution chest computed tomography scan showed well‐defined multiple centrilobular nodules and a tree‐in‐bud pattern. Chest auscultation revealed coarse crackles. He did not report any nasal sinus symptoms. We subsequently performed a video‐assisted lung biopsy; the specimen confirmed diffuse panbronchiolitis. Subsequently, sinusitis was confirmed by an otolaryngologist. His symptoms gradually improved following treatment with erythromycin. We report a case of early‐stage diffuse panbronchiolitis in a young patient, with multiple intralobular nodules, no bronchiectasis, and a good clinical course.